Peran Pendidik Dalam Pendidikan Islam: (Kajian Konseptual Hadist-Hadist Tarbawi) - Marzuki, Jaeni; Mirza, Iskandar; Saefurridjal, Ahmad (Indonesian Journal of Islamic Education Studies (INJURIES), 2024)
The role of the educator is the most important thing in the continuity of learning, so it must be given an important role in Islamic Education. Many studies on the role of educators do not explicitly describe the nature of educators themselves. The aim of this research is to describe the nature of educators, the characteristics of educators, the duties and obligations of educators, and the role of educators in Islamic education. The approach taken in this study uses a qualitative approach with library research methods. Data collection techniques were obtained from journals, e-books, magazines, newspapers, and the hadith books of Politikus Sittah, (the book of Sahih Bukhari, the book of Sahih Muslim, the book of Sunan Abu Daud, the book of Sunan Turmudzi, the book of Sunan Al-Nasa'i, the book of Sunan Ibn Majjah and Ususut tarbiyah Islamiyah Fi Sunnatin Nabawiyyah). Meanwhile, the analysis technique used is a descriptive analysis by comparing the findings, then the results are studied in depth starting from the position of hadith, Matan hadith, and sanad hadith and used as new findings. The results of this research show that based on the interpretation of the Prophet's hadiths the role of educators is very important, including; educators as Facilitators, Motivators, Inspirators, Mentors, sparking students' imagination and creativity, Developing character values and teamwork, social empathy. Keywords: Role of Educator; Islamic Education; Hadith Tarbawi